Anaphylaxia to opioids in a pediatric oncological patient, case report - Díaz Medina, Adrián (2020)
We present a case of a patient with a diagnosis of acute lymphoblastic leukemia and trisomy 21, who was hospitalized for initiation of management with first-line chemotherapy in whom there were various complications during his treatment that required both antibiotic and opioid analgesic management. Subsequently develops four allergic-type reactions, three of them were associated with opioids and the last of them classified as severe angioedema related to the administration of tramadol. The presentation of the clinical case is made, due to the low incidence of occurrence of severe allergic reactions to opioids, particularly to tramadol in the context of a highly complex patient receiving multiple medications.